Accuracy and complications of CT-guided pulmonary core biopsy in small nodules: a single-center experience - Huang, Ming-De (Cancer Imaging, 2019)
BACKGROUND: Computed tomography (CT)-guided pulmonary core biopsies of small pulmonary nodules less than 15 millimeters (mm) are challenging for radiologists, and their diagnostic accuracy has been shown to be variable in previous studies. Common complications after the procedure include pneumothorax and pulmonary hemorrhage. The present study compared the diagnostic accuracy of small and large lesions using CT-guided core biopsies and identified the risk factors associated with post-procedure complications. METHODS: Between January 1, 2016, and December 31, 2017, 198 CT-guided core biopsies performed on 195 patients at our institution were retrospectively enrolled. The lesions were separated into group A (< or = 15 mm) and group B (> 15 mm) according to the longest diameter of the target lesions on CT. Seventeen-gauge introducer needles and 18-gauge automated biopsy instruments were coaxially used for the biopsy procedures. The accuracy and complications, including pneumothorax and pulmonary hemorrhage, of the procedures of each group were recorded. The risk factors for pneumothorax and pulmonary hemorrhage were determined using univariate analysis of variables. RESULTS: The diagnostic accuracies of group A (n = 43) and group B (n = 155) were 83.7 % and 96.8 %, respectively (p = 0.005). The risk factors associated with post-biopsy pneumothorax were longer needle path length from the pleura to the lesion (p = 0.020), lesion location in lower lobes (p = 0.002), and patients with obstructive lung function tests (p = 0.034). The risk factors associated with post-biopsy pulmonary hemorrhage were longer needle path length from the pleura to the lesion (p < 0.001), smaller lesions (p < 0.001), non-pleural contact lesions (p < 0.001), patients without restrictive lung function tests (p = 0.034), and patients in supine positions (p < 0.003). CONCLUSION: CT-guided biopsies of small nodules equal to or less than 15 mm using 17-gauge guiding needles and 18-gauge biopsy guns were accurate and safe. The biopsy results of small lesions were less accurate than those of large lesions, but the results were a reliable reference for clinical decision-making. Understanding the risk factors associated with the complications of CT-guided biopsies is necessary for pre-procedural planning and communication.